Do clinical trials improve quality of care? A comparison of clinical processes and outcomes in patients in a clinical trial and similar patients outside a trial where both groups are managed according to a strict protocol. Issue 3 (2nd June 2005) - West, J; Wright, J; Tuffnell, D; Jankowicz, D; West, R
Abstract : Background: The conventional view that participants in randomised controlled trials sacrifice themselves for the good of future patients is challenged by increasing evidence to suggest that individual patients benefit from participation in trials. Objective: To test the hypothesis that trial participants receive higher quality care and, as a consequence, have better outcomes than patients receiving guideline driven routine care. Methods: Retrospective comparative study of 408 women with pre-eclampsia all managed according to a strict protocol. Trial participants were 86 women who participated in a multicentre randomised controlled trial of magnesium sulphate for the treatment of pre-eclampsia (Magpie Trial); 322 non-participants formed the control group. Indicators of the process of care and clinical outcomes were compared between the two groups. Results: Trial participants were significantly more likely to have received daily blood tests (odds ratio (OR) 6.82, 95% CI 1.62 to 28.72) and had their respiration rate measured hourly (OR 3.42, 95% CI 1.69 to 6.92) than control patients. There were no significant differences in other markers of clinical process and no significant difference in clinical outcomes. Conclusion: This study shows minor differences in process markers and no difference in clinical outcomes between patients in a clinical trial and patients receiving protocol driven care. The benefits of improved clinical care that have previously been associated with being in a trial may be explained by the use of clear clinical protocols. In routine practice, patients may be well advised to insist on treatment as part of a protocol.